КЛИНИЧЕСКИЕ ОСОБЕННОСТИ ТЕЧЕНИЯ АСТРАХАНСКОЙ РИККЕТСИОЗНОЙ ЛИХОРАДКИ В ЭКЗАНТЕМАТОЗНОМ ПЕРИОДЕ В ЗАВИСИМОСТИ ОТ ВОЗРАСТА - Н. Р. Бедлинская (Архивъ внутренней медицины, 2012)
In the last quarter of the twentieth century in various parts of the world there was a significant increase in the frequency of natural-focal rickettsioses, united in a group of tick-borne spotted fevers. The analysis of duration of symptoms in groups of patients with middle severity of illness of Astrakhan rickettsial fever (ARF) depending on age has shown that at patients with ARF is more senior 50 years the long period of an intoxication, longer terms eruption on the top extremities, rash occurrence on the face, the longer duration of pain in muscles, and also lymphadenitis and hepatic augmentation were marked.